Seebeck Coefficient Enhancement of ALD PbTe/PbSe Nanolaminate Structures Deposited inside Porous Silicon Templates. (29th July 2016) - Chen, Xin; Lin, Pengtao; Zhang, Kai; Baumgart, Helmut; Geist, Brian; Kochergin, Vladimir
Abstract : In this paper, lead chalcogenide based thermoelectric nanolaminate structures were fabricated by alternately depositing PbTe and PbSe ALD layers on regular planar silicon wafers and on microporous silicon templates. Lead bis(2, 2, 6, 6-tetramethyl-3, 5-heptanedionato) (Pb(C11 H19 O2 )2 ), plus (trimethylsilyl) telluride ((Me3 Si)2 Te) and (trimethylsilyl) selenide ((Me3 Si)2 Se) were used as the chemical ALD precursors for lead, tellurium and selenium, respectively. The Seebeck coefficient in horizontal direction (parallel direction to the surface) to the multiple layered PbTe/PbSe nanolaminate structures was measured by an MMR Seebeck system, and benchmarked against the Seebeck coefficient in the vertical direction to the sample surface. The results of the Seebeck measurements clearly indicate that the multiple layered PbTe/PbSe nanolaminate structures synthesized by ALD on microporous silicon templates exhibit significantly increased Seebeck coefficients in both horizontal and vertical directions, in stark contrast to the case when the same ALD thermoelectric nanolaminates are grown on regular planar bulk Si substrates.